Konstruksi Hubungan Hukum Dalam Skema Perjanjian Produk Asuransi Yang Dikaitkan Dengan Investasi (PAYDI) - Alya Rosana; Arief Suryono (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
Investment-linked insurance, otherwise known as unit-linked insurance, offer attractive potential benefits because in addition to providing life protection, they also offer investments for policyholders. However, it also involves the construction of complex legal relationships between policyholders and insurance companies. The purpose of this study is to determine and analyze the construction of legal relationships in insurance schemes linked to investment. This research uses normative legal research methods through data collection techniques in the form of literature studies. The approach used is the statute approach. The results show that the unit-linked insurance agreement scheme involves at least two key elements, namely policyholders and insurance companies. Policyholders can choose to invest their funds in financial instruments managed by investment managers. The legal relationship between the parties is based on an insurance contract known as a policy. The insurance policy regulates the rights and obligations of each party. Premiums paid by policyholders are allocated to the basic premium for insurance protection and investment premiums. Meanwhile, the insurance company provides a return on the premium in the form of life protection and investment management.